Java interview guide : 200+ questions and answers - Karanam, Ranga; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2018)
"Preparing for Java Interview is tricky. You need to have a good understanding of the new features and revise concepts you used in your preparation. This course helps you to prepare for Java interviews with hands-on code examples covering 200+ Java interview question and answers on a varied range of topics."--Resource description page.
Title from resource description page (Safari, viewed April 3, 2018).
Presenter, Ranga Karanam.
Keywords: Java (Computer program language); Application software -- Development; Web site development; Employment interviewing; Electronic books